Characterization of untreated and treated recycled copper powder filled epoxy/poly (methyl methacrylate) (pmma) composites - Mohamad Nur Fuadi Pargi (School of Materials Engineering, 2016)
In this study, recycled copper filled epoxy composites were characterized based on its mechanical, electrical and thermal properties. The effects of different particle sizes of recycled copper were filled with epoxy to investigate the effect of mechanical, electrical and thermal properties. Testing such as morphology, mechanical testing, coefficient of thermal expansion determination, thermogravimetric analysis and electrical conductivity measurement were done to study the properties of the composites. The particle size of recycled copper was determined by using particle size analysis. X-ray diffraction (XRD) analysis was performed in order to analyse the element of the recycled copper. Flexural test was carried out to investigate the flexural properties: flexural strength and flexural modulus of epoxy composites. Besides that, Vickers hardness and density testing were performed to study the physical properties of epoxy composites. Furthermore, coefficient of thermal expansion (CTE) analysis was carried out to investigate the thermal property of epoxy composites. The electrical property was performed in order to measure the electrical conductivity of epoxy composites.